Forecasting of municipal solid waste generation in Türkiye and techno-economic-environmental assessment of electricity generation via incineration till 2032 - Mehmet Melikoglu (Next Sustainability)
This paper develops a forecasting model for municipal solid waste (MSW) generation and its potential for energy recovery through incineration in Türkiye. MSW generation in 81 provinces of Türkiye are forecasted till 2032 using novel semi-empirical models based on two different scenarios. It is forecasted that Türkiye’s MSW generation in 2032 will reach up to 36.2 million tonnes and from incineration of this MSW up to 16.8 TWh of electricity worth 2.1 billion US$ (based on 2024 June wholesale industrial prices) can be generated. Nationwide greenhouse gas (GHG) emissions from incineration of MSW for electricity generation can reach 19.7 million tonnes of carbon dioxide in 2032. Root mean squared error and mean absolute percentage error values indicated high goodness of fit and accuracy for the forecasting models. As future research it is suggested that the methodology given in this study can be used by others for forecasting MSW generation with energy recovery as electricity via incineration and associated GHG emissions calculations in different countries conditional that historic geographical per capita data is available and associated model parameters are calculated based on existing circumstances.